Enhancing Intrusion Detection in Electric Networks Using Physics-Informed Random Forest - Bozdal, Mehmet; Savasci, Alper (Institute of Electrical and Electronics Engineers Inc., 2024)
The increasing complexity of electric power networks has heightened their vulnerability to cyber-attacks, challenging traditional Intrusion Detection Systems (IDS) that rely on manually crafted rules. This paper introduces a novel approach that integrates physics-informed features and feature selection into a Random Forest (RF) model to enhance IDS performance. By deriving features such as complex power and impedance from fundamental electrical principles and applying SelectKBest for optimal feature selection, our method not only improves detection accuracy but also enhances efficiency by using fewer than half the features. Specifically, the feature-enriched RF model utilizing 55 features achieves an accuracy of 0.9667 and an F1-score of 0.9664, compared to 0.9576 and 0.9570 for the baseline RF model. This approach demonstrates the effectiveness of advanced feature engineering and selection techniques for improving the security and reliability of power network monitoring systems. © 2024 Elsevier B.V., All rights reserved.
IEEE SMC; IEEE Turkiye Section
Keywords: Cybersecurity; Electric Networks; Intrusion Detection Systems; Physics-Informed Features; Random Forest; Cyber Attacks; Cyber Security; Cyber-Attacks; Electric Power Networks; Features Selection; Intrusion Detection Systems; Intrusion-Detection; Physic-Informed Feature; Random Forest Modeling; Random Forests; Systems Performance; Network Intrusion